Age- and sex-based differences in the moral intuitions of American early adolescents. (27th July 2022) - Bretl, Brandon L.; Goering, Marlon
Abstract: Abstract: This study sought to explore the validity of a latent-factor model of moral intuition development during early adolescence. The 3-Factor Character Foundations Survey (CFS-3) was used to assess the moral intuitions of early adolescents ( n = 850, mean = 12.4 years old, SD = 0.96) under a moral foundations theory framework. Confirmatory factor analysis supported the psychometric validity of the three latent factor constructs (autonomy, loyalty and empathy), and partial metric invariance was established to allow for the comparison of latent factor means between four age- and sex-based groups coinciding with averages for pubertal onset. Results support prior findings of greater latent factor means for females in all three factors when compared with males in the 11–12-year-old age group. Additionally, 13–14-year-old females exhibited lower latent factor means in autonomy and loyalty factors when compared with 11–12-year-old females. This resulted in 13–14-year-old females remaining higher in empathy and autonomy but showing no difference in loyalty when compared with 13–14-year-old males. The results are interpreted through the lens of attachment theory, socio-cultural influence and certain limitations of the survey instrument itself. Suggestions for future studies are proposed.